QSAR Studies of Some Pharmacologically important Compoundsfor SARS CoV - Veena Saluja; Pradeep Kumar Gupta; Yashaswina Arora; Kishor Arora (International Journal of Pharma and Bio Sciences, 2020)
Currently, the outbreak of the novel human respiratory coronavirus, also popularly known as COVID-19, has sought the attention of the scientific community across the world and stresses on the need for new therapeutic alternatives in order to cease the global health crisis and fight the pandemic. The situation, therefore, calls out for new researchcentred on targeting the pathogen. A number of studies reveal the potential of different chemical moieties that could possibly act against the virus. In our work, we report the semi-empirical based 3D -QSAR 3D-quantitaive structure and activity relationship / QSAR studies of 3 series of compounds viz. Ethacrynic Acid Derivatives (E1-E3), Isatin (2,3-oxindole) Inhibitors (I1-I7) and Flavonoid and Biflavonoid Derivatives (F1-F7) on the basis of their reported activities against SARS Co-V. The studies are carried out on Hyperchem 8.0 version software using AM1 and PM3 methods. Selected QSAR/ 3D-QSAR equations including different physical parameters of these series are reported.